PENGARUH MOTIVASI INTRINSIK TERHADAP PRESTASI KERJA KARYAWAN BATIK NAKULA SADEWA SLEMAN YOGYAKARTA - Armansyah Armansyah (Program Studi Manajemen, 2020)
The main problem in this research is whether there is an influence of Intrinsic motivation (achievements, recognition of others, work itself, opportunities for development, responsibility) partially on the work performance of employees of Batik Nakula Sadewa Sleman Yogyakarta and whether there is intrinsic motivation (achievements achieved) , recognition of others, work itself, opportunities for development, responsibility) simultaneously on the work performance of employees of Batik Nakula Sadewa Sleman Yogyakarta. The research objective was to partially determine the effect of intrinsic motivation (achievement achieved, recognition of others, work itself, opportunities for development, responsibility) on work performance of employees of Batik Nakula Sadewa Sleman Yogyakarta and to see the effect of intrinsic motivation (achievement achieved, recognition of others, work itself, opportunities for development, responsibility) simultaneously on the work performance of employees of Batik Nakula Sadewa Sleman Yogyakarta. The sample population in this study were all employees of Batik Nakula Sadewa Sleman Yogyakarta which can be said to be 35 employees. Sampling technique is to use saturated sampling technique. The analytical tool used is multiple regression analysis, F test, and t test. The test results with the t test and the F test prove that the Intrinsic Motivation variable (achievement, recognition of others, the job itself, opportunities for development, responsibility) has a positive effect on the Employee Performance of Batik Nakula Sadewa Sleman Yogyakarta..